EFEKTIVITAS PENERAPAN SISTEM TANGGAP DARURAT RUNWAY EXCURSION PADA PT ANGKASA PURA I (PERSERO) BALIKPAPAN - Siboro, Impol; Zainul, L.M; Sunyanti, Sunyanti; Syarif, Nur Fadly (Program Studi Kesehatan dan Keselamatan Kerja, 2023)
Aviation safety is a very important factor in every flight operation. This study aims to determine the Effectiveness of the Implementation of the Runway Excursion Emergency Response System at PT. Angkasa Pura I (Persero) Sultan Aji Muhammad Sulaiman Sepinggan-Balikpapan International Airport in tackling Incident/Accident at the Airport. The benefit of this research is to add insight and knowledge of researchers about the Effectiveness of the Implementation of the Runway Excursion Emergency Response System and as an evaluation material on the Effectiveness of the Implementation of the Runway Excursion Emergency Response System at the Airport, especially Sultan Aji Muhammad Sulaiman Sepinggan-Balikpapan International Airport. This research method uses descriptive qualitative with collecting techniques from observations and interviews. The location of this research was conducted at PT. Angakasa Pura I Airport Branch Office of Sultan Aji Muhammad Sulaiman Sepinggan-Balikpapan International Airport, especially in the Airport Rescue And Fire Fighting Services unit. The conclusion of this study is based on data collected from 3 predetermined variables, namely: response team, quality and quantity of PKP-PK personnel and PKP-PK Emergency Response Facilities. So, the average result is obtained with the achievement of a percentage value of 81.33% or in the level of effectiveness the result is